Personal accounts from Northern Ireland's troubles : public conflict, private loss - Smyth, Marie, 1953-; Fay, Marie-Therese, 1973- (Pluto Press, 2000)
This poignant collection of first-hand accounts brings the personal toll of the Troubles to life. We hear about multiple bereavement from Margaret, personal injury from an RUC officer, and participation in a hunger strike from a former IRA member.